Acute Kidney Injury Sensitizes the Brain Vasculature to Ang II (Angiotensin II) Constriction via FGFBP1 (Fibroblast Growth Factor Binding Protein 1). Issue 6 (December 2020) - Zhao, Liang; Cao, Xiaoyun; Li, Lingli; Wang, Xiaohua; Wang, Qin; Jiang, Shan; Tang, Chun; Zhou, Suhan; Xu, Nan; Cui, Yu; Hu, Weipeng; Fei, Lingyan; et al.
Abstract : Acute kidney injury (AKI) causes multiple organ dysfunction. Here, we identify a possible mechanism that can drive brain vessel injury after AKI. We induced 30-minute bilateral renal ischemia-reperfusion injury in C57Bl/6 mice and isolated brain microvessels and macrovessels 24 hours or 1 week later to test their responses to vasoconstrictors and found that after AKI brain vessels were sensitized to Ang II (angiotensin II). Upregulation of FGF2 (fibroblast growth factor 2) and FGFBP1 (FGF binding protein 1) expression in both serum and kidney tissue after AKI suggested a potential contribution to the vascular sensitization. Administration of FGF2 and FGFBP1 proteins to isolated healthy brain vessels mimicked the sensitization to Ang II after AKI. Brain vessels in Fgfbp1 −/− AKI mice failed to induce Ang II sensitization. Complementary to this, systemic treatment with the clinically used FGF receptor kinase inhibitor BGJ398 (Infigratinib) reversed the AKI-induced brain vascular sensitization to Ang II. All these findings lead to the conclusion that FGFBP1 is especially necessary for AKI-mediated brain vascular sensitization to Ang II and inhibitors of FGFR pathway may be beneficial in preventing AKI-induced brain vessel injury. Abstract : Supplemental Digital Content is available in the text.